Isolation and Identification of a Novel Anti-protein Aggregation Activity of Lignin-Carbohydrate Complex From Chionanthus retusus Leaves - Pei, Wenhui; Chen, Zhefan Stephen; Chan, Ho Yin Edwin; Zheng, Liming; Liang, Chen; Huang, Caoxing (Frontiers in Bioengineering and Biotechnology, 2020)
Lignin-carbohydrate complex (LCC) is the biological macromolecule that has been demonstrated to exert multiple biological functions, including antioxidant, anti-inflammation and anti-tumorigenesis, which support its broad application in the bioengineering field. However, it remains elusive the involvements of LCC in human neurological disorders, especially those with the overproduction of reactive oxygen species, such as spinocerebellar ataxias (SCAs). In this study, we found a previously undetermined anti-protein aggregation activity of LCC. Initially, two individual LCC preparations and carbohydrate-free lignin were isolated from the water-extracted waste residues of Chionanthus retusus (C. retusus) tender leaves. The chemical compositional analysis revealed that lignin (61.5%) is the predominant constituent in the lignin-rich LCC (LCC-L-CR), whereas the carbohydrate-rich LCC (LCC-C-CR) is mainly composed of carbohydrate (60.9%) with the xylan as the major constituent (42.1%). The NMR structural characterization showed that LCC-L-CR preparation is enriched in benzyl ether linkage, while phenyl glycoside is the predominant type of linkage in LCC-C-CR. Both LCC and lignin preparations showed antioxidant activities as exemplified by their abilities to scavenge free radicals in cultured mammalian cells and reactive oxygen species in zebrafish. We further demonstrated a pronounced capability of LCC-L-CR in inhibiting the aggregation of expanded Ataxin-3, disease protein of SCA type 3, in human neuronal cells. Taken together, our study highlights the antioxidant and novel anti-protein aggregation activities of the C. retusus tender leaves-derived LCC.